Towards dissecting molecular routes of intercellular communication in the tumour microenvironment: phenotypic plasticity of stem cell-associated markers in co-culture (carcinoma cell/fibroblast) systems - Fík, Z; Dvořánková, B; Kodet, O; Bouček, J; Betka, J A; Betka, J; André, S; Gabius, H-J; Šnajdr, P; Smetana, K; Chovanec, M (Folia biologica, 2014)
Increasing evidence attributes tumour fates to a small population of cells (cancer stem cells) capable of surviving therapeutic interventions. Investigation of their characteristics, especially in cross-talk with other cell types of the tumour microenvironment, can pave the way to innovative therapeutic concepts. The central issue of this study was to evaluate the impact of stroma on tumour cells with stem cell-like features in a squamous cell carcinoma model (FaDu). Six different types of experimental conditions were tested using distinct compositions of the culture system, and both morphologic and molecular features of the tumour cells were analysed. In detail, FaDu cells alone were used as a control, compared to tumour cells from co-culture, with squamous cell cancer-derived stromal fibroblasts or normal skin human fibroblasts, both in the direct and indirect (insert) systems, adding analysis of side population cells of FaDu culture. Measurements were taken on days 2, 7 and 9 of culture and immediately after preparation in the case of the side population. A panel of antibodies against keratins 8, 10, 19, stem cell markers CD29, CD44, CD133, as well as biotinylated adhesion/growth-regulatory galectin 1 served as a toolbox for phenotypic characterization. Co-culture with fibroblasts prepared from tumour stroma and with dermal fibroblasts affected marker presentation, maintaining an undifferentiated stage phenotypically related to stem cells. Side-population cells showed close relationship to cancer stem cells in these characteristics. In conclusion, normal and tumour stromal fibroblasts are capable of shifting the marker expression profile of FaDu cells to a stem cell-like phenotypic pattern in co-culture.
Keywords: Coculture Techniques; kokultivační techniky; nádorové mikroprostředí; fenotyp; fibroblasty; nádorové kmenové buňky; nádorové buněčné linie; lidé; Phenotype; Neoplastic Stem Cells; Tumor Microenvironment; Biomarkers, Tumor; Cell Line, Tumor; Fibroblasts; nádorové biomarkery; Humans; mezibuněčná komunikace; Cell Communication